Stratospheric ozone depletion - Middlebrook, Ann; Tolbert, Margaret (University Science Books, 2000)
This module discusses the discovery of the Antarctic ozone hole, scientific studies of the processes that cause stratospheric ozone loss, and the international strategy to protect the ozone layer for future generations. The module forms part of a series created during the Global Change Instruction Program (GCIP). This series has been designed by college professors to fill an urgent need for interdisciplinary materials on global change. These materials are aimed at undergraduate students not majoring in science. The modular materials can be integrated into a number of existing courses—in earth sciences, biology, physics, astronomy, chemistry, meteorology, and the social sciences.